Theoretical systematization of data mining in the marketing area - Sarzosa Rivera, Soledad (2019)
The research is aimed at carrying out a theoretical systematization of data mining in the marketing area, through a bibliographic review in various databases and with the support of the Perish tool. It is concluded that data mining is a vital tool within companies and specifically in the area of marketing, because it determines patterns of behavior and purchase of customers, supports in making decisions, prevents them from being wrong, minimizes risks and takes advantage of the resources of the companies.